Adapting the Entrepreneurship Model to End Poverty in Sabah - Dasan, Jakaria; Wahab, Mat Salleh@Salleh; Madli, Faerozh; Gulabdin, Shaierah; Thomas, Bibianah (Journal of Technical Education and Training, 2025)
Sabah’s poverty issue becomes the focus of the study due to the high incidence of poverty rate. The government made several attempts, most of which were unsuccessful. To solve this challenge, effective entrepreneurial effort is required. APPGM-SDGs have been created to address this problem. The study aims to adapt the proper entrepreneurship initiative model by employing a qualitative method through focus group discussions. Using six impact evaluation indicators (Deep, Clear, Wide, High, SDG, Gender) as a guide, 10 beneficiary groups from 10 distinct districts participated in the FGDs. Interviews with beneficiaries— mostly entrepreneurs— were conducted to learn how they reacted to the models of eradicating poverty. The progress report created by the solution providers was also cross-checked as part of the data collection process. Although SHARE Model may be useful in identifying the good potential projects before the project commencement, it must also consider ROI and ROV. Noteworthy, incorporating TVET components and ensuring alignment with pertinent SDGs are imperative for entrepreneurs. TVET institutions are therefore actively encouraged to develop close relationships with the community. Additionally, TVET reduces costs, saves time, and streamlines the process. The current study purposely focuses on the main issue related to SDG 1 (No Poverty). Reports from the ten projects representing the Sabah West region become the main reference of the study. The fact that so few of them can link the relevant SDG to the initiative suggests that the community's awareness of SDGs is inferior. Previous experiences engaging in various community projects and past research argued that understanding SDGs has to be parallel with gaining the required knowledge of entrepreneurship. Henceforth, learning what the community is lacking and understanding the return of value to any project of SDGs might elevate the community’s socioeconomics.